EFFECT OF ADDITIVES ON DISSOLUTION CHARACTERISTICS OF FUROSEMIDE-POLYVINYLPYRROLIDONE SOLID-DISPERSION SYSTEMS - (:unkn) unknown (ECV-EDITIO CANTOR VERLAG MEDIZIN NATURWISSENSCHAFTEN, 1991)
The effect of additive type and concentration on drug dissolution from furosemide: PVP solid-dispersion systems has been studied. Avicel PH101, Ac-Di-Sol, Primojel, Kollidon CL and Aerosil were examined as additives. Two different drugs: PVP ratios (1:2 and 1:6) were used and additives were added in low and high concentrations (2 % and 20 %). Furosemide-PVP solid dispersion systems are sensitive to the incorporation of additives. Kollidon CL is the best additive for furosemide-PVP solid-dispersion systems. A retardant effect was observed by the addition of Ac-Di-Sol. Furthermore, the effect of Avicel PH101, Primojel and Aerosil depends on furosemide: PVP ratio and also concentration of additives.
Keywords: DIURETICS; FUROSEMIDE-PVP, DISSOLUTION CHARACTERISTICS, EFFECT OF ADDITIVES; SOLID-DISPERSION